Association between disease activity and quality of life among patients with rheumatoid arthritis - Rômulo Lopes da Costa; Felício de Freitas Netto; Diogo von Gaevernitz Lima; Fabiana Postiglione Mansani; Marcelo Derbli Schafranski; Bruno Queiroz Zardo; Alceu de Oliveira Toledo Júnior; Lorena de Freitas Calixto; José Carlos Rebuglio Vellosa; Elisangela Gueiber Montes (Universidade de São Paulo, 2023)
Abstract The aim of this study is the association between the scores of disease activity, functional capacity and quality of life among patients diagnosed with rheumatoid arthritis, under clinical treatment at the Regional University Hospital of Campos Gerais - Wallace Thadeu de Mello and Silva. The sample was composed by volunteer patients, who freely underwent 3 research questionnaires. With the results of the survey, the disease activity score was correlated to the functional capacity and the quality-of-life scores. A mean of 3.87 and 1.2 was observed for the disease activity and the functional capacity scores, respectively, yet not achieving a correlation between those two variables. A strong correlation between the disease activity and the "functional capacity", "general health status" and "mental health" domains was found. The lowest average observed corresponded to "physical limitation", from the quality-of-life questionnaire. There was no statistically significant correlation between disease activity and functional capacity, although disease activity seems to affect the mental health, general health status and functional capacity of patients.